1980
DOI: 10.1128/jb.143.1.221-230.1980
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Rhodopseudomonas sphaeroides chromatophore membrane asymmetry through bilateral antiserum adsorption studies

Abstract: The asymmetric structure of the Rhodopseudomonas sphaeroides chromatophore membrane was examined in detail by crossed immunoelectrophoresis techniques. Because these methods are quantitative and allow increased resolu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

1982
1982
1995
1995

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…about 20% of the reduced pyridoxine 5'-phosphate conjugates at the periplasmic aspect of the ICM were exposed in the isolated chromatophores. This agrees with previous findings (3,12) that about 80% of such chromatophores are isolated as sealed vesicles with their cytoplasmic aspect exposed and suggests further that the majority of the periplasmic aspect of the ICM was surface labeled by this procedure.…”
Section: Resultssupporting
confidence: 93%
“…about 20% of the reduced pyridoxine 5'-phosphate conjugates at the periplasmic aspect of the ICM were exposed in the isolated chromatophores. This agrees with previous findings (3,12) that about 80% of such chromatophores are isolated as sealed vesicles with their cytoplasmic aspect exposed and suggests further that the majority of the periplasmic aspect of the ICM was surface labeled by this procedure.…”
Section: Resultssupporting
confidence: 93%
“…5), although the evidence in this case is indirect. The membrane topology of the photosynthetic reaction center has been determined in several bacteria (16,42,183,231,240,257). In the organisms examined, one or more of the reaction center subunits (H, M, or L) are exposed at the periplasmic surface of the membrane.…”
Section: Methods Of Enzyme Localizationmentioning
confidence: 99%
“…Assays of ferrocytochrome c photo-oxidation in the presence and absence of octyl-,f-D-glucopyranoside suggested that these preparations consist of -900% 'inside-out' ICM vesicles with the cytoplasmic aspect of the ICM exposed [20]. Preparation of spheroplasts Spheroplasts were prepared essentially as described previously [21]. Photoheterotrophically grown cells were pelleted and washed twice with 1 mM Tris/HCl, pH 7.5, resuspended to an A680 of 6.5 in 50 mM Tris/HCI, pH 7.5, containing 25 % (w/v) sucrose, and stirred at room temperature for 10 min, followed by addition of 0.1 vol.…”
Section: Introductionmentioning
confidence: 99%